2008
DOI: 10.1211/jpp.60.7.0009
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Nrf2-antioxidant system by a novel cyclooxygenase-2 inhibitor furan-2-yl-3-pyridin-2-yl-propenone: implication in anti-inflammatory function by Nrf2 activator

Abstract: Furan-2-yl-3-pyridin-2-yl-propenone (FPP-3) is a novel synthetic compound and has demonstrated anti-inflammatory activity by inhibiting cyclooxygenase-2 (COX-2). It is widely accepted that reactive oxygen species (ROS) generated by activated inflammatory cells can exacerbate inflammation. In this study, the potential antioxidative efficacy of FPP-3 has been investigated in murine cells. FPP-3 increased the expression of multiple antioxidative enzymes, including NAD(P)H:quinone oxidoreductase 1 (Nqo1), g-glutam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Consistent with the data published by others, we found that two cancer related genes, COX-2 and Bcl-XL, were upregulated in UVA irradiated HaCaT cells 44, 50, 51 ; 49, 52 . Notably, expression of both genes is dependent upon activation of p38, since inhibition of p38 with SB202190 abolishes their induction in UVA irradiated HaCaT cells 44, 49 .…”
Section: Signaling Pathways Activated By Uva In Human Kertinocytessupporting
confidence: 93%
“…Consistent with the data published by others, we found that two cancer related genes, COX-2 and Bcl-XL, were upregulated in UVA irradiated HaCaT cells 44, 50, 51 ; 49, 52 . Notably, expression of both genes is dependent upon activation of p38, since inhibition of p38 with SB202190 abolishes their induction in UVA irradiated HaCaT cells 44, 49 .…”
Section: Signaling Pathways Activated By Uva In Human Kertinocytessupporting
confidence: 93%
“…Moreover, FPP‐3 was shown to inhibit NF‐κβ activation in vitro leading to the decrease of iNOS expression and TNF‐α biosynthesis . Finally, a variety of other beneficial actions of FPP‐3 have been reported, such as chemopreventive effects, antioxidant properties, and anti‐angiogenic actions, broadening the spectrum of potential application for this drug …”
Section: Identification Of Novel Targets In the Arachidonic Acid Cascadementioning
confidence: 99%
“…Flavonoids, including flavones, flavanols and condensed tannins, are plant secondary metabolites and these phenolic compounds have redox properties, which allow them to act as antioxidants [23]. Furthermore, flavonoids activate Antioxidant Responsive Element (ARE) through Nrf2 pathway to counteract proinflammatory mediator such as TNF α and COX induced inflammation [24][25][26].…”
Section: Total Flavonoid and Phenolic Contentsmentioning
confidence: 99%
“…Thanks to activation of aredox-sensitive gene regulatory network mediated by the NF-E2-related factor-2 (Nrf2) which is involved in response tooxidativestress and xenobiotics, mediatedthrough Antioxidant Responsive Element (ARE). Phenolic compounds such as flavonoids activates Antioxidant Responsive Element (ARE) through Nrf2 pathway to counteract proinflammatory induced inflammation [24][25][26]. Similarly, phenolics countering oxidative stress invarious pathological condition, few to be mentioned as in cancer cell lines and hypoxia for this reason increasingly being used as therapeutic agent.…”
Section: Antioxidant Activitymentioning
confidence: 99%